Anthina flammea Fr. (Deuteromycota, Fungi) en El Bierzo (León, N.O. España). - Bello, Justina; Lence, Carmen; Acedo, Carmen (Acta Botanica Malacitana, 2009)
Anthina flammea Fr. (Deuteromycota, Fungi) from El Bierzo (León, NW Spain) Palabras clave. Anthina flamea, Deuteromycota, hongos mitosporicos, León, España. Keywords. Anthina flamea, Deuteromycota, mitosporic fungi, León, Spain.